Influence of water compartmentation and heterogeneous relaxation on quantitative magnetization transfer imaging in rodent brain tumors. Issue 2 (16th September 2015) - Li, Ke; Li, Hua; Zhang, Xiao‐Yong; Stokes, Ashley M.; Jiang, Xiaoyu; Kang, Hakmook; Quarles, C. Chad; Zu, Zhongliang; Gochberg, Daniel F.; Gore, John C.; Xu, Junzhong
Abstract : Purpose: The goal of this study was to investigate the influence of water compartmentation and heterogeneous relaxation properties on quantitative magnetization transfer (qMT) imaging in tissues, and in particular whether a two‐pool model is sufficient to describe qMT data in brain tumors. Methods: Computer simulations and in vivo experiments with a series of qMT measurements before and after injection of Gd‐DTPA were performed. Both off‐resonance pulsed saturation (pulsed) and on‐resonance selective inversion recovery (SIR) qMT methods were used, and all data were fit with a two‐pool model only. Results: Simulations indicated that a two‐pool fitting of four‐pool data yielded accurate measures of pool size ratio (PSR) of macromolecular versus free water protons when there were fast transcytolemmal exchange and slow R1 recovery. The fitted in vivo PSR of both pulsed and SIR qMT methods showed no dependence on R1 variations caused by different concentrations of Gd‐DTPA during wash‐out, whereas the fitted kex (magnetization transfer exchange rate) changed significantly with R1 . Conclusion: A two‐pool model provides reproducible estimates of PSR in brain tumors independent of relaxation properties in the presence of relatively fast transcytolemmal exchange, whereas estimates of kex are biased by relaxation variations. In addition, estimates of PSR in brain tumors using the pulsed and SIR qMT methods agree well with one another. Magn Reson Med 76:635–644, 2016. © 2015 Wiley Periodicals, Inc.